Classical Trade Protectionism 1815-1914 - Dormois, Jean-Pierre (Routledge Explorations in Economic History, 2006)
Including contributions from such figures as Douglas Irwin, James Foreman-Peck, Kevin O'Rourke and Max-Stefan-Schulze, this key book summarizes the recent empirical research carried out on the issue of the classical period of trade protectionism. It provides a basis for revising widely held views on the standard effects of tariffs on economic structures and progress, as well as a historical perspective on recent developments. Long-held views on modern trade policies have been challenged by the introduction of recent theoretical developments in international economics and in measurement techniques brought about in the 1960s and 70s. One question in particular has attracted attention and has contributed to the bringing to light of a number of previously ignored measurement and interpretation problems: the assessment of French and British nineteenth century trade policies. This noteworthy volume examines the theoretical and practical problems associated with the assessment and measurement of the direct impact of tariffs, prohibitions and quotas on domestic prices, output structure and competitiveness. The contributors also examine the direct and long-run consequences of protectionist measures on particular economies, utilizing evidence from in-depth investigations of trade statistics as well as 'best practice' statistical techniques such as effective protection, elasticity of demand and revealed comparative advantage.